ANALISIS PENGARUH FAKTOR INTERNAL BANK TERHADAP JUMLAH PENYALURAN KREDIT PADA BANK UMUM KONVENSIONAL DI INDONESIA - Galih Sulistio, 10.05.52.0003; Lisiantara, Greg. Anggana (Students Journal of Accounting and Banking, 2014)
This study aims to examine the influence of internal factors analysis of the number of lending banks on Conventional Banks in Indonesia are listed in Bank Indonesia (BI) in the year 2008 to 2011 includes a factor of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Return on Assets (ROA), Loan to Deposit Ratio (LDR), and Operational Efficiency (BOPO). The sample used 78 Bank and hypothesis testing using t-test with a significance level of 5 %.Based on the results of that study showed a significant positive impact deposits, CAR significant negative effect, NPL is no significant negative effect, ROA is no significant positive effect, LDR is no significant negative effect, BOPO is no Â significant negative effect.Keywords: Credit, Third Party Funds, Capital Adequacy Ratio, Non-Performing Loan, Return on Assets, Loan to Deposit Ratio, Operational Efficiency